2010
DOI: 10.1039/c0sc00271b
|View full text |Cite
|
Sign up to set email alerts
|

End-functionalized glycopolymers as mimetics of chondroitin sulfate proteoglycans

Abstract: Glycosaminoglycans are sulfated polysaccharides that play important roles in fundamental biological processes, such as cell division, viral invasion, cancer and neuroregeneration. The multivalent presentation of multiple glycosaminoglycan chains on proteoglycan scaffolds may profoundly influence their interactions with proteins and subsequent biological activity. However, the importance of this multivalent architecture remains largely unexplored, and few synthetic mimics exist for probing and manipulating glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 36 publications
1
78
0
Order By: Relevance
“…37 We chose this exo -norbornene 4 because it has been reported that 4 undergoes ring-opening metathesis polymerization (ROMP) much faster than its endo -counterpart, 38 and allows for multivalent display of the ligands at defined, chemically controlled intervals to promote multivalent binding. 39 Furthermore, this polymerizable scaffold 4 increases the structural rigidity of the neoglycopolymers and allows efficient access to the corresponding copolymers between α-mannose and β-glucose units. 39 Accordingly, the Mitsunobu coupling of 4 with alcohol linker 5 40 provided 6 in 98% yield (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 We chose this exo -norbornene 4 because it has been reported that 4 undergoes ring-opening metathesis polymerization (ROMP) much faster than its endo -counterpart, 38 and allows for multivalent display of the ligands at defined, chemically controlled intervals to promote multivalent binding. 39 Furthermore, this polymerizable scaffold 4 increases the structural rigidity of the neoglycopolymers and allows efficient access to the corresponding copolymers between α-mannose and β-glucose units. 39 Accordingly, the Mitsunobu coupling of 4 with alcohol linker 5 40 provided 6 in 98% yield (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…39 Furthermore, this polymerizable scaffold 4 increases the structural rigidity of the neoglycopolymers and allows efficient access to the corresponding copolymers between α-mannose and β-glucose units. 39 Accordingly, the Mitsunobu coupling of 4 with alcohol linker 5 40 provided 6 in 98% yield (Scheme 1). Removal of the tert -butyl silyl (TBS) ether group afforded 82% yield of primary alcohol 7 , which served as a glycosyl acceptor in the glycosylation with trichloroacetimidate donor 8 mediated by 20 mol% of trimethylsilyl triflate (TMSOTf).…”
Section: Resultsmentioning
confidence: 99%
“…[11,13,33] Fig. 4 Glycopolymer-based glycoarray: a duel end functionalized mucin like glycopolymer with alkyne on one end and Texas Red dye on the other end [24], b mucin like glycopolymer presentation that mimics native mucin [40], c biotin end functionalized glycopolymer immobilized glass slide [26], d glycopolymer formation at different illumination times [41], e O-cyanate end functionalized glycopolymer immobilized on amine functionalized glass slide [27], f O-cyanate chain-end functionalized glycopolymer pre-complexed and immobilized with boronic acid ligands of different sizes [28]. Modified from Ref.…”
Section: Glycopolymer-based Glycan Microarraymentioning
confidence: 99%
“…Hsieh-Wilson et al synthesized a biotin end functionalized glycopolymer that mimic chondroitin sulfate proteoglycans via ring-opening metathesis polymerization technique [26], which were employed for microarray and SPR applications. Both sulfated CS-E and non-sulfated CS-C glycopolymers were immobilized onto streptavidin coated glass slides by high-precision contact-printing robot, which delivers nanoliter volumes of glycopolymer onto glass slides.…”
Section: Glycopolymer-based Glycan Microarraymentioning
confidence: 99%
See 1 more Smart Citation